Correlation Between Total Bilirubin, Total Bilirubin/Albumin Ratio with Disease Activity in Patients with Rheumatoid Arthritis - Zhang H; Yang G; Jiang R; Feng D; Li Y; Chen Y; Yuan G (International Journal of General Medicine, 2023)
Hui Zhang,1,* Guizhao Yang,1,* Rongqiong Jiang,1 Dan Feng,1 Yuqin Li,1 Yong Chen,2 Guohua Yuan1 1Institute of Rheumatism and Immunology, the Affiliated Hospital of North Sichuan Medical College, Nanchong, People’s Republic of China; 2Department of Rheumatism and Immunology, the People’s Hospital of Jianyang City, Jianyang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guohua Yuan, Institute of Rheumatism and Immunology, the Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, People’s Republic of China, Tel +8615983777907, Fax +8608172262301, Email ghyuan1981@139.comPurpose: Rheumatoid arthritis (RA) is a systemic inflammatory disorder with unknown etiology. Oxidative stress and immune imbalance play a critical role in the pathogenesis of rheumatoid arthritis. Bilirubin has recently been recognized as a potent antioxidant as well as an immunomodulatory agent of physiological importance. The aim of this study was to explore whether increased bilirubin concentrations are correlated with good clinical prognosis of rheumatoid arthritis.Patients and Methods: In this cross-sectional study, we included 197 healthy individuals and 197 RA patients in the Affiliated Hospital of North Sichuan Medical College from October 2020 to February 2022. The latter were classified into three classes of disease activity according to DAS28-ESR: remission and low (DAS28-ESR< 3.2), moderate (3.2≤DAS28-ESR≤ 5.1), and high (DAS28ESR> 5.1). Based on the clinical and laboratory data, we evaluated the association of bilirubin levels with disease activity in RA using multivariable ordered logistic regression.Results: The levels of total bilirubin and total bilirubin/albumin ratio were significantly lower (P < 0.001; P < 0.001) in RA patients compared with healthy controls. In RA patients, Spearman’s rank correlation analysis revealed that bilirubin and total bilirubin/albumin ratio were negatively correlated with disease activity and inflammatory marker (C-reactive protein, erythrocyte sedimentation rate, Interleukin-6). In multivariable ordered logistic regression, higher total bilirubin (OR=0.77, 95% CI: 0.67– 0.89, p< 0.001) independently predicted lower disease activity.Conclusion: Bilirubin levels remain associated with a reduction of disease activity, suggesting that bilirubin may be a protective factor for RA aggravation.Keywords: rheumatoid arthritis, bilirubin, bilirubin/albumin ratio, diagnostic marker, multivariate analysis